First Record of Liocheles nigripes (Pocock, 1897) (Scorpiones: Hemiscorpiidae) from Chhattisgarh, with Comments on its Distribution - Zambre, Amod; Patil, Sunny (Journal of the Bombay Natural History Society (JBNHS), 2011)
No Abstract.